A Novel Universal Applicability Design Method for Low Cross-Polarization Terahertz Tri-Reflector CATR. (15th November 2022) - Li, Zhi; Yao, Yuan; Chen, Tianyang; Zhang, Liang; Yu, Junsheng; Chen, Xiaodong
Abstract : In this paper, a novel design approach with universal applicability is proposed for realizing a low cross-polarized terahertz tri-reflector compact antenna test range (CATR). This approach not only enables the radiation direction of the feed relative to the main reflector to be designed arbitrarily but also enables the designed CATR systems corresponding to different feed rotation angles while still maintaining a low cross-polarization. By using the beam mode analysis method and cross-polarization elimination conditions, the geometric configurations of the tri-reflector CATR can be designed for feeds in any different rotation angles, and then according to the kinematic and dynamic ray-tracing method with frequency independence in geometric optics, shaped subreflectors can also be synthesized. Through the above design procedure, four tri-reflector CATRs corresponding to four different feed rotation angles have been achieved, respectively. Numerical simulation results show that the cross-polarizations of four tri-reflector CATRs are all less than –38 dB and the peak-to-peak amplitude (phase) ripples of the quiet zone (QZ) are all within 1 dB (10°) in the frequency range of 100–500 GHz. This demonstrates the effectiveness and universal applicability of the proposed design method in realizing the design of low cross-polarization and good QZ performance for tri-reflector CATRs with different feed rotation angles.